Prevalence of removable partial dentures users treated at the Aracatuba Dental School - UNESP - Pellizzer, Eduardo Piza [UNESP]; Faria Almeida, Daniel Augusto de [UNESP]; Falcon-Antenucci, Rosse M. [UNESP]; Sanchez, Daniela Mayumi I. K. [UNESP]; Zuim, Paulo Renato Junqueira [UNESP]; Verri, Fellippo Ramos [UNESP] (Wiley-Blackwell, 2012)
Objectives: The aim of this study was to evaluate the frequency of removable partial dentures (RPD) at the Aracatuba Dental School.Methods: The study was conducted by analysing 412 clinical history of patients attended at the RPD clinics in the period from 2000 to 2007.Results: 412 charts were analysed: 148 (35.9%) men and 264 (64.1%) women. The mean age was 53.8 years (men) and 52.4 years (women). A total of 556 dentures were made; of these, 233 (41.90%) were maxillary and 323 (58.09%) were mandibular dentures. The most frequent Kennedy classification found was Class III (maxilla) and Class I (mandible). In the maxilla, 55% (126) of the major connectors were of the anterior-posterior palatal bar, while in the mandible, 64% (202) were the lingual bar. As regards the claps, 401 were circumferential and 318 were bar claps.Conclusion: The mean age of the patients was 52.9 years with higher prevalence of female patients; the most frequent Kennedy's classification was Class I in mandible and Class III in maxilla; the most common major connector was anterior-posterior palatal bar for maxilla and lingual bar for mandible; the circumferential clasps were the most common retainer used in both jaws.
Keywords: removable partial denture; Kennedy classification; denture construction